(untitled) (Research, Society and Development, 2023)
Congenital heart disease is any abnormality in the formation of a baby’s heart that occurs during pregnancy, influencing the structural and functional development of the circulatory system. The main point of this article is to address the psychological effects of the situation of congenital heart disease in children/adolescents, focusing mainly on how this reflects on their caregivers (in general, their parents). This is an narrative review focused on publications in the field of psychology about the effects of having a child who undergoes hospitalizations, invasive surgeries and the possibility of death on family’s relationships. It was observed that mothers are, in general, the main affected and that there is a change in family dynamics, sometimes permanently and difunctionally. The multidisciplinary work of psychologists and others from the hospital network are the main allies in the treatment of these families.